2022
DOI: 10.3126/medphoenix.v6i2.38371
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Dimensions and Variation on Computed Tomography Angiogram: A Cross-sectional Study.

Abstract: Introduction A knowledge of renal artery dimension is necessary for characterizing the physiological change as well as pathological process undergoing in the renal artery likely stenosis, ectasia, or aneurysm. This study aims to explore the anatomy of the renal artery with regards to its dimension, relation, and branching and identify the common anatomical variation. Materials and Methods The study was a retrospective hospital record-based study conducted during the period of one year from 2019 January to 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…10,14,19 However, Jamkar AA et (75.01%), Cinar C et al (68.7%),Reginelli A et al (69%), Pradhav G et al (70%), Pant OB et al (67%) and Chhetri PK et al (67.76%) found higher prevalence of normal renal arterial system. 2,7,13,15,16,17 In our study, male and females had similar number of renal arterial variations. Similar findings were reported in studies by Palmiri BJ et al, Cinar C et al, Reginellia A et al and Chhetri PK et al 5,7,13,17 However, Gumus H et al found significantly higher variations in male cases.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…10,14,19 However, Jamkar AA et (75.01%), Cinar C et al (68.7%),Reginelli A et al (69%), Pradhav G et al (70%), Pant OB et al (67%) and Chhetri PK et al (67.76%) found higher prevalence of normal renal arterial system. 2,7,13,15,16,17 In our study, male and females had similar number of renal arterial variations. Similar findings were reported in studies by Palmiri BJ et al, Cinar C et al, Reginellia A et al and Chhetri PK et al 5,7,13,17 However, Gumus H et al found significantly higher variations in male cases.…”
Section: Discussionsupporting
confidence: 60%
“…Similar findings were reported by Pant OB et al (89.1%), Chhetri PK et al (72%) and Toro JSC et al (77%). 16,17,18 The incidence was higher on right side as compared to left (54.54% right and 45.58% left). Studies by Chhetri PK et al (54.84% right and 45.16 % left) and Pradhav G et al also found higher incidence of right sided renal arterial variations.…”
Section: Discussionmentioning
confidence: 94%